Potential barriers to rapid testing for human immunodeficiency virus among a commuter population in Johannesburg, South Africa - Tshuma, N.; Muloongo, K.; Setswe, G.; Chimoyi, L.; Sarfo, B.; Burger, D.; Nyasulu, P.S. (HIV/AIDS - Research and Palliative Care, 2015)
Background: This study aimed to determine barriers to accessing human immunodeficiency virus (HIV) counseling and testing (HCT) services among a commuter population.Methods: A cross-sectional, venue-based intercept survey was conducted. Participants were recruited during a 2-day community campaign at the Noord Street taxi rank in Johannesburg, South Africa. Data were collected using a self-administered questionnaire loaded onto an electronic data collection system and analyzed using Stata software. Factors contributing to barriers for HCT were modeled using multivariate logistic regression.Results: A total of 1,146 (567 male and 579 female) individuals were interviewed; of these, 51.4% were females. The majority (59.5%) were aged 25–35 years. Significant factors were age group (15–19 years), marital status (married), educational level (high school), distance to the nearest clinic (.30 km), area of employment/residence (outside inner city), and number of sexual partners (more than one). Participants aged 15–19 years were more likely to report low-risk perception of HIV as a barrier to HCT (odds ratio [OR] 1.62; 95% confidence interval [CI] 1.01–2.59), the married were more likely to report low-risk perception of HIV as a barrier to HCT (OR 1.49; 95% CI 1.13–1.96), and those living outside the inner city were more likely to report lack of partner support as a potential barrier (OR 1.94; 95% CI 1.34–2.80), while those with a high school education were more likely to report poor health worker attitude as a potential barrier to HIV testing (OR 2.17; 95% CI 1.36–3.45).Conclusion: Age, marital status, occupation, educational level, area of employment and residence, distance to the nearest clinic, and number of sexual partners were factors significantly associated with barriers to HIV testing in the study population. Future HIV intervention targeting this population need to be reinforced in order to enhance HIV testing while taking cognizance of these factors. © 2015 Tshuma et al.
Keywords: Accessibility; Commuter; Counseling; Human immunodeficiency virus; Population; Testing